Proceedings of the 1st ACM Workshop on Emerging Name-Oriented Mobile Networking Design - Architecture, Algorithms, and Applicat 2012
DOI: 10.1145/2248361.2248367
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic content sharing applications

Abstract: Opportunistic communication between mobile nodes allows for asynchronous content sharing within groups. Limiting the spread of information to a geographic area creates an infrastructure-less variant of digital graffiti, a social network with coupling in space and limited decoupling in time. Due to its nature, this kind of a communication network lends itself readily to name-oriented abstractions. In this paper, we extend our previous work on floating content, extract its fundamental characteristics, and define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 31 publications
(34 reference statements)
0
27
0
Order By: Relevance
“…In our previous work [15], we showed that acquisition times for content upon a node entering an anchor zone are typically a few minutes. In [15] we also presented example applications and we now contrast them against the results in this paper, in particular the square mobility case.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In our previous work [15], we showed that acquisition times for content upon a node entering an anchor zone are typically a few minutes. In [15] we also presented example applications and we now contrast them against the results in this paper, in particular the square mobility case.…”
Section: Discussionmentioning
confidence: 98%
“…In [15] we also presented example applications and we now contrast them against the results in this paper, in particular the square mobility case.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Delay-tolerant networking between mobile nodes exploiting opportunistic contacts between the devices as their users move around has been a research topic for many years, yielding diverse communication and software architectures [23,4,21,14], a myriad of routing protocols, and a diverse set of applications [1,20,7,6,13,8,9], to name just a few.…”
Section: Introductionmentioning
confidence: 99%